Strategi Komunikasi Pemasaran Coffee Toffee Madiun dalam Meningkatkan Jumlah Konsumen - Wicaksono, Mahesa Wahyu; Widiantari, Maria Magdalena; Sejati, Veny Ari (Universitas Pahlawan Tuanku Tambusai, 2025)
In today's modern era, business owners are required to be more astute in promoting and selling their products to compete with their competitors. Furthermore, they must be able to maintain the loyalty of existing customers and reach out to potential customers for business continuity. This study aims to analyze the marketing communication strategy implemented by Coffee Toffee SunCity Madiun to increase the number of customers. The research approach used a qualitative descriptive method and data collection techniques such as interviews, observation, and documentation. The results indicate that Coffee Toffee applies five main elements in its marketing communication strategy based on the Integrated Marketing Communication (IMC) theory. The implementation of this strategy has been quite effective in several months in building brand awareness, attracting new customers, and maintaining customer loyalty. Challenges faced include intense competition in the coffee shop industry. It is hoped that the results of this study can serve as a reference for business owners in developing appropriate and responsive marketing strategies